Determination of free radical scavenging activity, phenolic and flavonoid content of seven corn cultivars from the Southwest Maluku District, Indonesia - SINAY, HERMALINA (2022)
Sinay H, Mahulette F, YáñezJA. 2022. Determination of free radical scavenging activity, phenolicand flavonoid content of seven corn cultivars from the Southwest Maluku District, Indonesia.Biodiversitas 23:5974-5981.The variation of corn (Zea maysL.) kernel might be considered as a surrogate indicator of the phytochemical and bioactive content. This study aimed to determine the phenolics, flavonoids, and free radical scavenging activity of seven local corn cultivars from Kisar Island, Southwest Maluku District in Indonesia. Sample extraction was done by the maceration method. Flavonoid content wasdetermined using the Dowd method, and total phenolic content was performed using the Folin-Ciocalteu method. Free radical scavenging activity was determined using the DPPH radical scavenging method. One-way ANOVA was performed with Duncan multiple range tests to assess the differences between corn seed cultivars, and p < 0.05 were regarded as statistically significant. The results show that the total flavonoid content varied from 8.463 mg QE/mg (Putihcultivar) to 40.075 mg QE/mg (Kuning Dalamcultivar). Total polyphenol content also varied between 105.63 mg GAE/mg (Merah Delima Tongkol Putihcultivar) and 136.41 mg GAE/mg (Pulutcultivar). The antioxidant activity by DPPH assay determined that the seven local corn cultivars had IC50values that were similar to quercetin (used as control), some were even lower. The IC50value of the seven local corn cultivars ranged from 5.56 to 16.96 μg/mL, while quercetinhad an IC50value of 11.97 μg/mL. It was observed that theMerah Delima Tongkol Cokelat, Merah Delima Tongkol Putih,andPutihcultivars had comparable antioxidant activity to the control quercetin. TheMerah Darah, Kuning Genjah, andKuning Dalamcultivars exhibited a statistically significant higher antioxidant capacity than quercetin. These results can contribute to the selection of corn cultivars to harvest for commercial purposes and potential nutraceutical applications.